Atomic force microscopy : fundamental concepts and laboratory investigations - Sanders, Wesley Crowell (CRC Press, 2020)
"This book focuses primarily on the atomic force microscope, and serves as a reference for students, postdocs, and researchers using atomic force microscopes for the first time. In addition, this book can serve as the primary text for a semester long, introductory course in atomic force microscopy. There are a few algebra-based mathematical relationships included in this book that describe the mechanical properties, behaviors, and intermolecular forces associated with probes used in atomic force microscopy. To add, relevant figures, tables, and illustrations are in each chapter in an effort to provide additional information and interest. This book includes suggested laboratory investigations that provide an opportunity to explore the versatility of the atomic force microscope. These laboratory exercises include opportunities for experimenters to explore force curves, surface roughness, friction loops, conductivity imaging, and phase imaging"--